Pengaruh Financial Distress, Free Cash Flow dan Profitabilitas terhadap Earnings Management dengan Firm Size sebagai Moderasi - Inten Gemi Nestiti; Bambang Satriawan; Robin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted with the aim of testing and analyzing the influence of Financial Distress, Free Cash Flow and Profitability on Earnings Management moderated by Firm Size directly or indirectly. The population in this study were all construction companies listed on the Indonesia Stock Exchange, while the sample that met the criteria for drawing observations conducted for five years and as many as six pharmaceutical companies listed on the Indonesia Stock Exchange. This research approach uses quantitative research. The data collection technique in this study used documentation techniques and the analysis technique used was EViews (Econometric Views) analysis. The results of the study showed that the results of the first hypothesis test showed that financial distress had no significant effect on earnings management. The results of the second hypothesis test showed that free cash flow had a significant positive effect on earnings management. The results of the third hypothesis test showed that profitability had a significant positive effect on earnings management. The results of the fourth hypothesis test showed that financial distress had a significant effect on earnings management moderated by firm size. The results of the fifth hypothesis test showed that free cash flow had a significant effect on earnings management moderated by firm size. The results of the sixth hypothesis test showed that profitability had a significant effect on earnings management moderated by firm size.